2021
DOI: 10.3390/cancers13235874
|View full text |Cite
|
Sign up to set email alerts
|

The miR-200 Family of microRNAs: Fine Tuners of Epithelial-Mesenchymal Transition and Circulating Cancer Biomarkers

Abstract: The miR-200 family of microRNAs (miRNAs) includes miR-200a, miR-200b, miR-200c, miR-141 and miR-429, five evolutionarily conserved miRNAs that are encoded in two clusters of hairpin precursors located on human chromosome 1 (miR-200b, miR-200a and miR-429) and chromosome 12 (miR-200c and miR-141). The mature -3p products of the precursors are abundantly expressed in epithelial cells, where they contribute to maintaining the epithelial phenotype by repressing expression of factors that favor the process of epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 241 publications
(320 reference statements)
3
73
0
Order By: Relevance
“…Examination of miRNAs for specific fractions can significantly increase both the sensitivity and specificity of selected circulating miRNAs as noninvasive biomarkers [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ].…”
Section: Circulating Mirnamentioning
confidence: 99%
“…Examination of miRNAs for specific fractions can significantly increase both the sensitivity and specificity of selected circulating miRNAs as noninvasive biomarkers [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ].…”
Section: Circulating Mirnamentioning
confidence: 99%
“…In other words, the mesenchymal/EMT phenotype can revert to mesenchymal-epithelial transition. The miR-200 family can regulate EMT [ 73 , 74 ]. miR-200b plays a critical role in EMT by interacting with genes involved in EMT, including receptors, signaling, and the cell cycle [ 75 ].…”
Section: Mir-200 Family and Targets Of The Mir-200 Familymentioning
confidence: 99%
“…The miR-200 family has substantial influence on cancer cell motility and invasive behavior through the direct suppression of EMT and metastasis formation in different tumor types. Consequently, many studies have suggested that the miR-200 family has great potential to be key biomarkers in a variety of diseases, including cancer (recently reviewed in [ 199 ], Table 4 ) and neurodegenerative diseases [ 200 , 201 ]. For instance, a recent meta-analysis study encompassing 24 eligible breast cancer articles and 16,565 subjects showed a significant correlation between high miR-200s expression and the poor overall survival of breast cancer patients, while the downregulation of miR-200s was associated with the poor survival of triple-negative and luminal breast cancer patients [ 202 ].…”
Section: Mir-200 Family As Predictive Markersmentioning
confidence: 99%